Henoch-Schönlein purpura and meningococcal B vaccination. Issue 3 (23rd July 2008) - Sexton, K; McNicholas, A; Galloway, Y; Radke, S; Kieft, C; Stehr-Green, P; Reid, S; Neutze, J; Drake, R
Abstract : The risk of Henoch-Schönlein purpura (HSP) following vaccination with a group B meningococcal vaccine was assessed through active hospital safety monitoring. There was no increase in the relative incidence of HSP within 30 days after vaccination nor recurrence in HSP cases who received one or more further vaccine doses (re-challenge).